2021
DOI: 10.3390/s21020395
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Method for the Impact Damage Segmentation of Curve-Shaped CFRP Specimens Inspected by Infrared Thermography

Abstract: Advanced materials such as continuous carbon fiber-reinforced thermoplastic (CFRP) laminates are commonly used in many industries, mainly because of their strength, stiffness to weight ratio, toughness, weldability, and repairability. Structural components working in harsh environments such as satellites are permanently exposed to some sort of damage during their lifetimes. To detect and characterize these damages, non-destructive testing and evaluation techniques are essential tools, especially for composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Hu et al [87] conducted a comparative analysis of POD based on RNCC after applying various types of signal processing to images acquired using the ECPT technique. Wei et al [88], by grafting a deep neural network to pulsed infrared thermography, conducted a study to detect impact damage of curved laminates exposed to a thermal stress cycle and subsequent ballistic impact and segment them into medium and long wave infrared sequences.…”
Section: Irt Utilized Deep Learningmentioning
confidence: 99%
“…Hu et al [87] conducted a comparative analysis of POD based on RNCC after applying various types of signal processing to images acquired using the ECPT technique. Wei et al [88], by grafting a deep neural network to pulsed infrared thermography, conducted a study to detect impact damage of curved laminates exposed to a thermal stress cycle and subsequent ballistic impact and segment them into medium and long wave infrared sequences.…”
Section: Irt Utilized Deep Learningmentioning
confidence: 99%
“…Lin et al [7] conducted a comparative analysis of the dynamic failure behavior of flat and curved panel structures of woven basalt/epoxy laminates under blast loading, emphasizing the important influence of structural curvature on the dynamic response. Wei et al [8] carried out experiments and numerical simulations on the high-speed penetration of laminates and concluded that, in addition to fiber failure, laminates under penetration loads also include spalling and matrix cracking. Penetration velocity, penetration angle, fiber layup, and laminate structure form generate rich research results on the dynamic behavior and failure of laminate structures under tensile loads [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the investigations on flat plates, there are also approaches for the thermographic investigation of curved surfaces. Wei et al used pulse thermography to investigate impact damage on a curved CFRP specimen that was exposed to both thermal loads and ballistic impacts [21]. Both principal component analysis (PCA) and specially trained neural networks were able to detect the damage.…”
Section: Introductionmentioning
confidence: 99%